A simplified single transseptal puncture approach using high-density 3D voltage mapping for atrial fibrillation ablation: acute complications and long-term results - Silva Cunha, Pedro; Teixeira, Bárbara Lacerda; Laranjo, Sérgio; Portugal, Guilherme; Valente, Bruno; Delgado, Ana Sofia; Pereira, Mariana; Rocha, António Condeixa; Brás, Manuel; Cruz, Madalena Coutinho; Paulo, Margarida; Lousinha, Ana; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: An ablation catheter and a circular mapping catheter requiring a double transeptal puncture (TSP) for left atrial access have been conventionally used for atrial fibrillation (AF) ablation. Recently, different operators have combined a single transseptal puncture technique with 3D high-density mapping catheters for pulmonary vein isolation (PVI). Objective: This study aims to compare two strategies, single versus double TSP, regarding the duration of the procedure, radiation time, complication rates, and outcomes. Methods: retrospective analysis of a large cohort of consecutive patients that underwent first PVI with radiofrequency energy (RF), using a point-by-point strategy, with a 3D mapping system, either with single or double TSP, according to the operator´s choice. Results: 285 patients with a mean age of 59.5 ± 11.6 years (36.5% female, 67.7% paroxysmal AF) underwent a point-by-point catheter ablation with RF between July 2015 and March 2020. The mean CHA2DS2-VASc score was 1.7 ± 1.3. Single TSP was performed in 115 (40.3%) patients and double TSP in 170 (59.6%). The operator´s experience (≥5 years of AF ablation procedures) was equally distributed among the two groups. The average procedure time ( 133± 31.7 minutes vs 123 ± 35.5 minutes, for single and double TSP, respectively) did reach a statistical difference between both groups (p = 0.008), but there was a substantial advantage regarding fluoroscopy time (13 ± 6.3min. vs 19 ± 9.1 min., for single and double TSP, respectively; p < 0.001). Acute major complications present similar rates in both groups (2.6% vs 2.3%, p=0.799). At the 2-year follow-up, both groups had a similar sinus rhythm maintenance rate (76.5% vs. 78.8%, p=0.646). Conclusion: A simplified single-TSP technique using high-density multi-electrode 3D mapping is a safe and highly successful option for AF ablation. This approach yields a substantial reduction in fluoroscopy time, with the potential to avoid acute complications, compared to a conventional double-TSP strategy.